Linguistic and textological analysis of the biblical concept «teshuqa» (תְּשׁוּקָה) in the context of the patristic tradition: the conception of gender equality - Lermontova, Tatyana N. (Journal of the Belarusian State University. Philology, 2025)
Linguistic and textological analysis of the biblical concept «teshuqa» (hebr. תְּשׁוּקָה) is conducted within the context of the patristic tradition. The etymology, semantics and contextual usage of this Hebrew word in the Old Testament, particularly in verse 16 of chapter 3 and verse 7 of chapter 4 of the Genesis, verse 10 of chapter 7 of the Song of Songs, are examined. Its rendering in the Synodal Bible translation and in the modern Russian translations, as well as in the Bible translations into Greek (the Septuagint) and Latin (the Vulgate) is compared. The main mechanisms of semantic transformation of the concept «teshuqa» in these languages are identified. It is demonstrated how they have influenced theological interpretations. Patterns of meaning transmission in biblical texts and their impact on exegesis are determined. The novelty of the work lies in the application of a comprehensive approach combining historical and philological, textological, comparative and linguistic methods, allowing a deeper understanding of the process of meaning change in religious terms within an intercultural context. The obtained results may be used for research in biblical studies, exegesis, ancient text translation, comparative lexicology and historical linguistics.
Keywords: teshuqa (תְּשׁוּקָה); etymology; semantics; historical linguistics; Bible translations; Septuagint; Vulgate; exegesis; patristic tradition